Learning Journey Towards Reconciliation: Developing Teacher Self-Efficacy - Biorn, Birgitte (Scholarship@Western, 2023)
Current changes in curriculum and provincial teaching standards are intended to address the Calls to Action from the Truth and Reconciliation Commission. Teachers are responsible for implementing the changes but do not yet have the knowledge or skills to effectively manage the transformative changes being suggested. This organizational improvement plan (OIP) aims to address the problem of practice associated with teacher efficacy to incorporate Indigenous-Informed pedagogy (IIP) using the collaborative model of professional learning communities (PLC). The triadic determination of beliefs, skills, and environment of social cognitive theory by Albert Bandura is highlighted as a necessary structure to ensure that when sources of self-efficacy are present, individuals will have a greater likelihood of success. The work of Indigenous scholar, Sandra Styres (2017), provides a necessary grounding of the change plan in the Hodenosaunee and Anishinaabe philosophies of Iethi'nihstenha Ohwentsia'kekha (Land). Styres’ (2017) circularity framework will guide all aspects of this OIP, including the implementation plan, and the communication plan with a thorough knowledge mobilization plan (KMb). Through transformative, adaptive, and authentic leadership, the leader will address the complex nature of the problem of practice, and the leader will use the spiral of inquiry (SOI) from Halbert and Kaser (2022) to monitor and evaluate the progress throughout the change process. Keywords: self-efficacy, transformative leadership, social cognitive theory, Indigenous-informed pedagogy, adaptive leadership, authentic leadership